IPTEKS PENGENDALIAN INTERN ASET TETAP PADA PT. PLN (PERSERO) UP3 MANADO - Gerung, Ireyne Regina; Pontoh, Winston (Universitas Sam Ratulangi, 2018)
In carrying out all its operational activities, a company needs and has never been separated from the role of fixed assets. Fixed assets are one of the assets of a company that has a useful life of more than one year and has a large materiality value. At PT. PLN (Persero) UP3 Manado, fixed assets are one of the assets with a very large value of materiality. Therefore, it takes a control of fixed assets to maintain and secure fixed assets from possible errors, both recording errors and policies made on fixed assets themselves. PT. PLN (Persero) UP3 Manado Certainly has a variety of fixed assets that support all company activities. Internal control of fixed assets at PT. PLN (Persero) UP3 Manado has been running well. PT. PLN (Persero) UP3 Manado is very concerned about the elements in the control of inter-fixed assets. Even though he has performed his duties well, PT. PLN (Persero) UP3 Manado still must pay attention to all the elements that exist to avoid things that are detrimental to the company in this case PT. PLN (Persero) UP3 Manado.Keywords : fix assets, intern control.